O7C.6 Effectiveness of an audit-based occupational health and safety management system certification on firm injury rates in alberta, canada. (April 2019) - McLeod, Chris; Macpherson, Robert; Aderounmu, Adebayo; Quirke, Willianm; Koehoorn, Mieke
Abstract : Objectives: To determine if achieving an audit-based occupational health and safety management system certification (OHSMS) is associated with lower firm-level lost-time injury rates. Methods: Firm-level workers' compensation claims and OHSMS audit data were extracted from eligible industry sectors for the years 2000 to 2015. OHSMS and non-OHSMS firms were matched on observable baseline characteristics using coarsened exact matching methods. A difference-in-difference observational research design using population-averaged negative binomial regression models estimated the effect (incidence rate ratios (IRR) with 95% confidence intervals) of OHSMS certification on firm lost-time injury rates, adjusting for confounders. Models were stratified by industry sector and type of OHSMS (certification for small versus large firms). Results: The cohort included 14, 377 OHSMS firms matched to 11 338 non-OHSMS firms. Overall, OHSMS certification reduced lost time injuries (IRR: 0.86, 95% CI: 0.83–0.88), with a greater effect in 2011–15 (IRR: 0.79, 95% CI: 0.75–0.82). OHSMS certification was most effective in reducing injuries in the manufacturing (IRR: 0.75, 95% CI: 0.70–0.80), trade (IRR: 0.79, 95% CI: 0.73–0.86), and transportation (IRR: 0.80, 95% CI: 0.72–0.89) sectors. No effect was found in oil and gas (IRR: 1.05, 95% CI 0.91–1.20), business (IRR: 0.89, 95% CI: 0.89–1.10) and forestry (IRR: 1.05, 95% CI: 0.83–1.33) sectors. OHSMS certification for small firms was not associated with a reduction in injuries (IRR: 0.98, 95% CI: 0.91–1.06.) in contrast to OHSMS certification for large firms (IRR: 0.84, 95% CI: 0.82–0.87). Conclusions: OHSMS certification is effective in reducing firm injury rates. Effectiveness varied by sector, time period, and small or large firm certification. Sectoral differences in OHSMS effectiveness suggest that the ability to prevent hazards targeted by certification may vary by work environment. Further, small firm OHSMS certification may not be identifying safer firms.